2006
DOI: 10.1110/ps.051810106
|View full text |Cite
|
Sign up to set email alerts
|

Domain:domain interactions within Hop, the Hsp70/Hsp90 organizing protein, are required for protein stability and structure

Abstract: The major heat shock protein (Hsp) chaperones Hsp70 and Hsp90 both bind the co-chaperone Hop (Hsp70/Hsp90 organizing protein), which coordinates Hsp actions in folding protein substrates. Hop contains three tetratricopeptide repeat (TPR) domains that have binding sites for the conserved EEVD C termini of Hsp70 and Hsp90. Crystallographic studies have shown that EEVD interacts with positively charged amino acids in Hop TPR-binding pockets (called carboxylate clamps), and point mutations of these carboxylate cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 28 publications
2
39
0
1
Order By: Relevance
“…Similar results have been reported previously for the interaction of HOP with C-terminally truncated Hsp70 protein (13). Several other studies of the HOP-Hsp70 complex suggested the existence of secondary contacts strengthening the clamp-EEVD interaction between these proteins (9,35). Additionally, a model has been proposed in which the TPR domain is initially recognized by multiple Hsp70/Hsp90 sites, and this interaction is then secured by two-carboxylate clamp-EEVD motif interaction (11).…”
Section: Discussionsupporting
confidence: 84%
“…Similar results have been reported previously for the interaction of HOP with C-terminally truncated Hsp70 protein (13). Several other studies of the HOP-Hsp70 complex suggested the existence of secondary contacts strengthening the clamp-EEVD interaction between these proteins (9,35). Additionally, a model has been proposed in which the TPR domain is initially recognized by multiple Hsp70/Hsp90 sites, and this interaction is then secured by two-carboxylate clamp-EEVD motif interaction (11).…”
Section: Discussionsupporting
confidence: 84%
“…Hop is a 60-kDa homodimer that links Hsp70 and Hsp90, central components of the regulation of CFTR trafficking, and it Co-IP's with CFTR (3). In addition, Hop is involved in cell-cycle regulation and steroid receptor maturation (24,34,35), and it is homologous to the CHIP complex, of importance to CFTR degradation (36). Hop has a conserved cysteine (C403) (23,24) located in an S-nitrosylation motif believed to be relevant to S-nitrosylation (26).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, whether IFIT2 acts as an adaptor protein between heat shock proteins and CK18 to modulate the activity of CK18 needs to be addressed. Although the detailed mechanism of IFIT2-cytokeratin interactions is unknown, tetratricopeptide repeat -containing proteins have been shown to associate with heat shock protein 70 and heat shock protein 90 and act as cochaperones to regulate protein structure, stability, and degradation (28).…”
Section: Discussionmentioning
confidence: 99%